Development and physicochemical analysis of coalho chesse added in siriguela leaves (Spondias purpurea) (Research, Society and Development, 2021)
Coalho cheese is produced from the coagulation of milk by specific enzymes or by means rennet, which is widely used in the state of Ceará, mainly in the Vale do Jaguaribe region. One option to enrich cheeses with compounds that are beneficial to the consumer's health is the addition of fruits, such as siriguela. Mainly the residues of this fruit such as pulp, peel, seeds and seriguela leaves (Spondias purpurea) have a composition rich in nutrients and, due to this, have great potential for application in food. Thus, this work aimed at the development of three type coalho cheese formulations varying the amounts of seriguela leaves, being: F1: 5g; F2: 10; F3: 15g. The cheeses were analyzed for pH, acidity, moisture, ash, protein, lipids. The pH tended to be neutral and it was observed that the acid content was above what is reported in the literature. The ash content was the only parameter that showed a significant difference by the Tukey test (p> 0.05), while the others had no significant variation. The cheese had low protein and lipid contents, being classified as lean, and consequently as low-calorie cheese, with moisture between medium and high, being necessary to be kept under adequate conditions of storage and handling to avoid contamination.